The Relationship Between The Sokoto Jihad and The Jijad of Al-Hajj 'Umar: An Assessment - Jah, Omar (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Relationship Between The Sokoto Jihad and The Jijad of Al-Hajj 'Umar: An Assessment